The Indispensable Dog - Wynne, Clive D. L. (Frontiers in Psychology, 2021)
Dogs’ remarkable success in living in a human-dominated world rests on a set of adaptations to cohabitation with humans. In this paper I review the nature of these adaptations. They include changes in reproductive and foraging behavior from their ancestor species, wolves, which can be understood as adaptations to the change from hunting live prey to feeding on human food residues. Dogs also show several changes in social behavior which are more controversial and even somewhat paradoxical. Contrary to theories of canine domestication which view dogs as less aggressive and more cooperative than wolves, several studies show that dogs’ social interactions with conspecifics are more hierarchical and competitive than are wolves’. As scavengers rather than hunters, dogs do not need to cooperate with conspecifics the way that wolves do. But how then can we understand dogs’ willingness to cooperate with humans? I propose an integrated account of dogs’ social behavior that does not assume that dogs need to recognize the species-identity of the individuals that they are in interaction with. Because of the overlap in formal signals of dominance and submission between dog and human and the complete control over resources dogs need that people hold, I propose that people occupy a status of “super-dominance” over dogs. This conception suggests several new lines of research which could shed light on the human-dog relationship to the benefit of both partners.